Alcohol and nicotine use among Polish undergraduate students – the preliminary results - Kawalec, Agata (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. “DiSCO” (Dietary Supplements Consumption of Undergraduate Students) study aimed to characterize the chosen elements of lifestyle among university students, including alcohol consumption and nicotine use. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The cross-sectional study was realized in cooperation with Italian Universities. The anonymous online survey was conducted from 01.02.2022 to 30.06.2023 among 294 Polish students (age range: 19-37): 202 women (mean age: 21.77; median: 21; SD: 2.46) and 92 men (mean age: 22.73; median: 22; SD: 2.89). The statistical analysis was performed with the use of Excel (Fisher’s exact test; Chi2 test; a significance level p<0.05) <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. 89.8% of students consumed alcohol in the last six months. 36.7% of students used tobacco products in the last year. The analysis of the frequency and type of nicotine products used and the frequency and circumstances of alcohol consumption by students did not reveal any significant differences among the sexes and age groups (p>0.05). Most of the students declared to occasionally use nicotine products (up to 3 times a week), most often traditional cigarettes or shredded tobacco. Most students consume alcohol 2–4 times a month, most often regardless of the meals. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Alcohol consumption and nicotine use among Polish students are similar in both sexes.